MENELAAH STRATEGI PEMBELAJARAN BAHASA DALAM DUNIA PENDIDIKAN AGAMA ISLAM - Wahdini Siregar; Badliatul Annisyah Dalimunthe; Sulham Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2025)
This research aims to determine the methods that teachers and parents can use in teaching Islam to improve students' Islamic character. Education is the main foundation in forming an individual's character, especially for students. Islamic religious education has a significant role in instilling noble values ​​in students from an early age, with the aim of producing a generation with noble character in accordance with Islamic teachings. This article explores the crucial role of Islamic Religious Education in developing positive character in students, as well as effective strategies for implementing language in the educational environment. First, Islamic Religious Education instills strong aqidah values ​​in students. This literature research uses qualitative methods. Data was collected through observation and surveys. Data analysis is carried out naturally without measuring observations in numbers with certain statistics. Some important people are internalized, while observations and interviews provide information about the main people responsible for caregiving. through early childhood parenting patterns, as well as techniques for instilling Islamic character traits in early childhood. The results of this research show that (1) Islamic religious education learning methods for teachers and parents improve the quality of Islamic character through example, direct teaching, praise, persuasion, good habits and memorization in schools, families and other places. in the form of independent, integrated and comprehensive learning activities; (2) Kindergarten aged children are educated with several important Islamic characteristics, such as monotheism education, faith, practice of worship and culture of etiquette, noble morals, and learning the Koran